A marca odebrecht como representação da corrupção corporativa: estudo de caso da imagem e reputação da empresa no âmbito da operação lava jato - FREITAS, DAELCIO DE (2020)
In the light of organizational communication, this dissertation aims to demonstrate how the Odebrecht brand may have become a representation of corruption in view of the publicity of the facts revealed by the Lava Jato operation that began with the investigation of crimes at Petrobras and extended to other spheres of the public-private relations. The possible rupture of the Odebrecht brand with public opinion may be the result of an attitude of confrontation with the facts revealed for almost a year, causing the corporate error to be reproduced in internal and external communication processes. The late recognition of errors, as well as the seriousness of the crimes revealed, produced thousands of negative reports, which may have canceled any credibility stock built by the group recognized for its engineering excellence and which has become one of the largest Brazilian multinationals. This work was carried out by reviewing the literature on public relations, organizational communication, reputation, crisis management and corporate governance activities, in addition to interviews with three executives who worked in the Odebrecht communication area. A survey carried out with 33 professionals who deal daily with the themes of organizational communication and reputation in universities, press vehicles, public relations / marketing agencies and companies also offer subsidies to confirm the hypothesis of this research, that the possibility that the Odebrecht brand has become a symbol of corporate corruption in the country's recent history. The author of this work was a communication employee of the Odebrecht group for more than nine years, having the opportunity to experience empirically before and during the Lava Jato crisis.